Response of Anthropogenic Volatile Organic Compound Emissions to Urbanization in Asia Probed With TROPOMI and VIIRS Satellite Observations. Issue 18 (22nd September 2022) - Pu, Dongchuan; Zhu, Lei; De Smedt, Isabelle; Li, Xicheng; Sun, Wenfu; Wang, Dakang; Liu, Song; Li, Juan; Shu, Lei; Chen, Yuyang; Sun, Shuai; Zuo, Xiaoxing; et al.
Abstract: Emissions of air pollutants and their precursors in urban air closely relate to urbanization involving economic development, population growth, and industrialization. Here we use formaldehyde (HCHO) columns from the TROPOspheric Monitoring Instrument (TROPOMI), night‐time light (NTL) radiance from the Visible Infrared Imaging Radiometer Suite, and population density data as respective proxies to explore how anthropogenic non‐methane volatile organic compound (NMVOC) emissions evolve with urbanization in Asia. HCHO columns correlate moderately to highly (0.64 ≤  r  ≤ 0.99) with the NTL radiance within most major Asian countries. On both national (across Asia) and provincial scales (within China), HCHO columns increase monotonically with NTL radiance or population density with a log‐linear pattern, implying anthropogenic NMVOC emissions in Asia may similarly respond to urbanization with no apparent turnover yet. Our study confirms TROPOMI HCHO columns as a proxy of anthropogenic NMVOC emissions. Plain Language Summary: We use multi‐source satellite remote sensing data and population density data to examine how anthropogenic non‐methane volatile organic compound (NMVOC) emissions evolve with urbanization in Asia. Anthropogenic NMVOC emissions (indicated by satellite formaldehyde columns) correlate moderately to highly with urbanization (indicated by night‐time light or population density) within most major Asian countries. We find a monotonic response between anthropogenic NMVOC emissions and urbanization in Asia, with no apparent turnover yet. Key Points: Satellite formaldehyde (HCHO) columns correlate moderately to highly with night‐time light radiance and population density in most major Asian countries A monotonic response between anthropogenic non‐methane volatile organic compound (NMVOC) emissions and urbanization may exist in Asia, with no apparent turnover yet TROPOspheric Monitoring Instrument HCHO column is confirmed as a reliable proxy of anthropogenic NMVOC emissions in Asia